The emergence of foot-and-mouth disease virus serotype O PanAsia-02 sub-lineage of Middle East–South Asian topotype in Bangladesh (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This research work was conducted for the molecular characterization of the circulating foot-and-mouth disease (FMD) virus in Bangladesh and revealed out their serotype.Materials and methods: The VP1 gene of six field isolates of FMD virus (FMDV) serotypes (two serotypes O, two serotypes A, and two serotypes Asia 1) was subjected for sequencing and phylogenetic analysis. Neighbor-joining trees were constructed by using the Molecular Evolutionary Genetics Analysis 6, having the field nucleotide sequences of FMDV and related sequences available in the GenBank.Results: The nucleotide sequences of the VP1 genes of serotypes O, A, and Asia-1 of the isolates revealed that overall isolates were 91%–100% similar to the isolates reported from Bangladesh and other neighboring countries. Among the isolates reported from Bangladesh, serotype O had 98%–100% identity, serotype A had 91%–100% identity, and serotype Asia-1 had 94%–100% identity. A phylogenetic analysis revealed that the FMDV serotype O PanAsia-02 sub-lineage was confirmed in Bangladesh under the Middle East–South Asian (ME-SA) topotype. On the other hand, we identified genotype VII (18) of Asia topotype (serotype A) and lineage C (serotype Asia-1).Conclusion: The FMDV serotype O PanAsia-02 sub-lineage was confirmed in Bangladesh under the ME-SA topotype for the first time. The extensive cross-border animal movement from neighboring countries may act as the source of diversified FMDV serotypes in Bangladesh.Adv. Vet. Anim. Res., 7(2): 360-366, June 2020